Air infiltration modelling based on low-pressure airtightness measurements - Vega Pasos, Alan Emmanuel (2020)
The building sector has been responsible for around 30% of carbon emissions. These emissions come from the construction materials, but mainly by the building operation. The largest energy user of a building usually is the Heating, Ventilation and Air Conditioning system (HVAC). The ventilation efficiency depends on a correct design; however there is an unintended part of the ventilation called air infiltration. One-third of the heating load of a building is related to infiltration. The fewer leakage paths the building envelope has, the less infiltration it will allow. These leakage paths define the airtightness of a building. Air infiltration mainly (but not only) depends on the airtightness.